Efektifitas Penyaluran Zakat Produktif dalam Bentuk Bantuan Modal Usaha terhadap Kesejahteraan Mustahik dengan Pendekatan Metode CIBEST - Clarashinta Canggih; Muhammad Bayu Dwie Saputra (Universitas Islam Lamongan, 2023)
This research aims at analyzing the impact of Productive zakat distribution on one's spiritual and material aspects. The impact is measured using the CIBEST technique which will produce spiritual value (SV) and material value (MV). This research aims at analyzing and cognizing its effectiveness perceived by mustahiq. The process is conducted by classifying it based on the quadrants in the CIBEST calculation technique, before or after giving productive zakat in the form of business capital assistance as one of Surabaya Infaq Management Institute (LMI). The research uses descriptive quantitative research method with 24 households as respondents. The results show that the provision of productive zakat in the form of business capital assistance has positive and effective impact on the economic and spiritual aspects of mustahiq with an increase from quadrant II to quadrant I.